The Associations between Attitude and Quitting Smoking in Adult Smokers: A Meta-Analysis - Anisah Firdaus; Lestari Indah; Bhisma Murti; Aem Ismail (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: According to the World Health Organization (WHO), by 2025, tobacco control initiatives are expected to reduce the prevalence rate of tobacco throughout the WHO region. Recent assessments of smoking epidemics over the past half-century show a decrease in overall smoking prevalence among adult males (32.2% to 33.1%) and females (6.3% to 6.7%). The effectiveness of all these smoking cessation programs depends on knowing the factors that affect smokers. Factors such as sociodemographic factors, attitudes, and environment play an important role in the desire to quit  smoking This study aimed to determine the influence of attitudes on the likelihood of quitting smoking in adults. Subjects and Method: Systematic review and meta-analysis using prism flow diagrams and PICO format. Population: Adult smokers. Intervention: attitudes of likelihood of quitting smoking, smoking Outcome: Smoking cessation behavior in adults. The online databases used are Google Scholar, BMC, ScienceDirect, and Springer Link with the words smoking cessation, attitude to quit smoking, cross sectional and aOR. There were 9 cross sectional studies published in 2019-2023. The analysis was performed with RevMan 5.3. Results: This meta-analysis included 9 cross-sectional studies  from the Hadiyah Zone, Southern Ethiopia, Bhubaneswar, India, Hanoi, Vietnam, United States, Saudi Arabia, England, Taiwan, Beirut, Lebanon and Qatar. The number of samples is 12,526. Smokers with positive attitudes were 1.28 times more likely to quit smoking than negative attitudes, and the effect was statistically significant (aOR= 1.28; CI 95%= 0.84 to 1.95; p= 0.260). Conclusion: Positive attitudes increase the likelihood of smokers quitting smoking.  Keywords: quit smoking, attitudes, smokers, cross sectional, aOR.